2020
DOI: 10.35564/jmbe.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Involvement of Students in Learning Business Economics Through Active Methodologies and Student Response Systems

Abstract: This work gathers an experience carried out during the academic years 2018-2019 and 2019-2020 in the Degree in Business Administration and Management in the Faculty of Economics and Business of the University of the Basque Country/Euskal Herriko Unibertsitatea (Gipuzkoa section). The main objective of the essay is to reinforce the involvement of students in the learning process and, secondly, to collect their perception of active methodologies for teaching-learning and thus be able to improve their application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Given the positive results regarding the methodology, as well as its assessment as a way of continuing learning in the context of a pandemic, we propose the model be adapted to use in face-to-face classroom settings, albeit in a controlled way [51].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Given the positive results regarding the methodology, as well as its assessment as a way of continuing learning in the context of a pandemic, we propose the model be adapted to use in face-to-face classroom settings, albeit in a controlled way [51].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In fact, this type of students has values, concerns, aspirations, way of learning, and even, a different brain structure, in this case due to their compulsive and constant use of mobile phones and screens (Bigné et al, 2019;Hutton et al, 2020;Jurayev, 2023), yet another proof, in this case tremendously objective, of previously mentioned differences. This situation has provoked that the techniques and methodologies currently used by professors, usually based on a more "traditional" or "classical" methodology (e.g., master lectures, repetition of concepts and memorization) are not fully effective, generating a palpable gap between the learning method used and the own students, often materialized through a lack of motivation, and therefore hindering their learning and attention capacity (Izagirre-Olaizola, et., 2020;Winquist & Carlson, 2014). This is why, educational institutions should know and be concerned about the typology of professors they have in their faculty, as well as the type of methodology they use in class (or will probably use regarding its characteristics) since, surprisingly, they could have great effects on the student motivation to obtain better academic results; but also on their preferences for receiving this content only from some of them (i.e., even though the content taught would be the same, students would not be indifferent in the way it is given/by the one who gives it).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on the effects of these type of platforms on classroom atmosphere demonstrated that it can encourage active student participation and increase student motivation towards learning the subject [9,10]. Furthermore, their use has been shown [11,12] to enhance collaborative learning during the learning process, which is linked in some way [9] to overall student academic performance.…”
Section: Introductionmentioning
confidence: 99%